PENGARUH PERNIKAHAN DINI TERHADAP TINGKAT PERCERAIAN DI KECAMATAN ABUNG BARAT - Muhammad Yunus; Abdul Aziz; Nurul Hasanah; Jama'atun Khasanah; A'im (Universitas Pahlawan Tuanku Tambusai, 2023)
Humans are created to live in this world in pairs that aim to complement each other’s deficiencies. Therefore, to form a bond both physically and mentally, the term marriage appears. Marriage is the only way of channeling sex that is legalized by the Islamic religion and the State of Indonesia. From this point of view, when a person is married at the same time he not only has the desire to carry out religious orders (shari’a), but also has the desire to fulfill his biological needs which by nature must be channeled. Recently, there have been many marriages carried out by young people who are still underage, which are known as early marriages. Early marriage is a phenomenon that has been rife for a long time in West Abung District, North Lampung Regency, Lampung Province. This type of research is field research (field research) using a qualitative research approach which is a technique, which will be the first step to collect in-depth data and information related to the problem the author is researching. Early marriages that are rife in society are motivated by many factors, both social, economic, educational, cultural, and the most common is promiscuity among adolescents. Society has different views on early marriage depending on what is behind the occurrence of the marriage. Based on the results of research and discussion on early marriage in West Abung District, North Lampung Regency, it was concluded that early marriages that occurred in West Abung District were motivated by various factors, namely promiscuity, the economy, lack of education and knowledge, arranged marriages, and social factors